Power quality measurements and operating characteristics of electric arc furnaces - Issouribehere, Fernando (2005)
Power quality is of increasing concern to utilities and their customer alike. Many loads connected to electric power systems can cause power quality problems at all voltage levels and for very different power ratings due to their unbalanced and non-linear behaviour characteristics. This paper describes the aspects of power quality at the point of common coupling (PCC) where an arc furnace for steel melting with alternating current is connected. By measurements of flicker, harmonics content in voltage and current, active and reactive power and power factor, the preservation of the reference levels for the supply voltage and emission limits for the furnace as a customer are evaluated. The evaluation of the power quality of contemporary International and Argentinian standards is given. The different phases in the operation of the arc furnace are described in detail and illustrated with measurements, and a complete single phase equivalent circuit for the arc furnace is obtained from field tests.